Exploring the role of delta-V in influencing occupant injury severities – A mediation analysis approach to motor vehicle collisions. (July 2020) - Shannon, Darren; Murphy, Finbarr; Mullins, Martin; Rizzi, Luis
Highlights: We examine the effect of motor vehicle collision (MVC) factors on the severity of injuries. Two approaches are considered: Log-linear Regression and Bayesian Probit Regression. delta-V plays a primary role in determining the number of injuries, and the probability of suffering an MAIS3+ injury. Some crash factors influence injury severity regardless of relative crash velocity (delta-V). Mediation approach unveils influential links that would have otherwise gone unnoticed. Abstract: This study investigates the impact that delta-V, the relative change in vehicle velocity pre- and post-crash, has on the severity of motor vehicle collisions (MVCs). We study injury severity using two metrics for each occupant – the number of injuries suffered, and the probability of suffering a serious or worse (MAIS 3+) injury. We use a cross-sectional set of generally-representative MVC data between 2010 and 2015 as a basis for our research. Collision factors that influence the crash environment are combined with the injuries that were suffered in MVCs. The influence of delta-V is captured using a mediation analysis, whereby delta-V acts as the focal point between crash factors and injury outcome. The mediation approach adds to existing research by presenting a detailed view of the relationship between injury severity, delta-V and other collision factors. We find evidence of competitive mediation, wherein a collision factor's positive association with injury severity is offset by a negative association with delta-V. Neglecting to include delta-V in our study would have let the factor's association with injury severity go undiscovered. In addition, certain collision factors are found to be related to injury severity solely because of delta-V, while others are found to have a significant impact regardless of delta-V. Our results support the multitude of policy recommendations that promote seatbelt use and warn against alcohol-impaired driving, and support the proliferation of safety-enabled vehicles whose technology can mitigate the bodily damage associated with detrimental crash types.